The I Ching : a biography - Smith, Richard J. (Richard Joseph), 1944- (Princeton, N.J. : Princeton University Press, 2012)
Relates the history of China's ancient divination manual, discussing its structure, worldwide appeal to different cultures, and influence on philosophy, medicine, art, and politics.
Part One. The domestic evolution of the Yijing -- Genesis of the Changes -- The making of a classic -- Interpreting the Changes -- Part Two. The transnational travels of the Yijing -- The Changes in East Asia -- The westward travels of the Changes -- Concluding remarks.
Includes bibliographical references (pages 251-264) and index.
Keywords: Yi jing